Vécu et contraintes lors de l’application d’une nou- velle approche pédagogique: Une étude de cas québécoise en comptabilité. - Coulombe, Daniel; Guilbert, Louise; Lacombe, Nicole; Mathieu, Robert; Racine, Helene (Canadian Journal of Higher Education, 2000)
This paper presents the experience of faculty members of the accounting department at Université Laval in designing and implementing a new curriculum. These changes have resulted from the new requirements of the profession as well as the growing gap between employers’ expectations and skills and professional attitudes of graduating accounting students. In addition to presenting the context of these changes, the paper discusses some of the difficulties faced during the implementation of the new curriculum and, more importantly, those faced when introducing a new teaching approach. The new curriculum is focused on a collaborative approach whereby student participation is solicited. However, several difficulties have been met during the implementation. For instance, faculty members face a higher level of uncertainty in the classroom and must devote more time in developing teaching material. Students’ perceptions, obtained through focus groups, were that the new program did not prepare them properly and that some courses were not useful. Throughout the paper, we offer some strategies that can be used to minimize the impact of the difficulties faced when implementing a new teaching approach that can overturn previously firmly held beliefs about appropriate pedagogical methods.